Praktik Jual Beli Buah Sistem Karungan Perspektif Kompilasi Hukum Ekonomi Syariah - Penti Vidiantika; Lia Noviana (Fakultas Syariah Institut Agama Islam Negeri Ponorogo, 2021)
There are various kinds of buying and selling activities in the Pulung market, starting from providing basic and secondary needs. Including buying and selling fruits with a sack system. In this sale and purchase, the collector does not provide a clear explanation of the quality of the object, so there are often discrepancies. This article aims to answer the following focus issues: First, it is related to how the Sharia Economic Law Compilation reviews the quality of objects in buying and selling fruit with the sack system. Second, it is related to how the Sharia Economic Law Compilation reviews the implementation of compensation in buying and selling fruit with the sack system at Pulung Ponorogo Market. This research includes field research using qualitative methods. While the data collection techniques used were observation, interviews, and documentation. From the results of this study, it can be concluded that the quality of objects in the sale and purchase of fruit with the sack system in the Pulung market, Pulung District, Ponorogo Regency is in accordance with KHES, because Article 76 of the KHES regarding the conditions for objects being traded has been fulfilled. And for the implementation of compensation in the sale and purchase of fruit with a sack system at the Pulung market, Pulung District, Ponorogo Regency, Article 77 of the KHES, because the collectors are already responsible and provide compensation for object defects. Terdapat berbagai macam kegiatan jual beli di pasar Pulung, mulai dari menyediakan kebutuhan pokok dan sekunder. Termasuk jual beli buah-buahan dengan sistem karungan. Dalam jual beli tersebut pihak pengepul tidak memberikan penjelasan mengenai kualitas objek dengan jelas, sehingga sering terdapat ketidaksesuaian. Artikel ini bertujuan menjawab fokus masalah berikut: Pertama, terkait bagaimana tinjauan Kompilasi Hukum Ekonomi Syariah terhadap kualitas objek dalam jual beli buah dengan sistem karungan. Kedua, terkait bagaimana tinjauan Kompilasi Hukum Ekonomi Syariah terhadap pelaksanaan ganti rugi dalam jual beli buah dengan sistem karungan di Pasar Pulung Ponorogo. Penelitian ini termasuk penelitian lapangan menggunakan metode kualitatif. Sedangkan teknik pengumpulan data yang dilakukan adalah menggunakan observasi, wawancara, dan dokumentasi. Dari hasil penelitian ini dapat disimpulkan bahwa kualitas objek dalam jual beli buah dengan sistem karungan di pasar Pulung Kecamatan Pulung Kabupaten Ponorogo sudah sesuai dengan KHES, karena sudah terpenuhi Pasal 76 KHES mengenai syarat obyek yang diperjualbelikan. Dan untuk pelaksanaan ganti rugi dalam jual beli buah dengan sistem karungan di pasar Pulung Kecamatan Pulung Kabupaten Ponorogo sudah dengan Pasal 77 KHES, karena pengepul sudah bertanggungjawab dan memberikan ganti rugi atas kecacatan obyek.